2013
DOI: 10.5433/1679-0359.2013v34n3p1111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aminoethoxyvinylglycine on biochemical, physicomechanical and colour properties of cv. Braeburn apples

Abstract: The effect of preharvest AVG (aminoethoxyvinylglycine) treatments on the biochemical, physicomechanical properties and colour characteristics of cv. Braeburn apples were determined. AVG was applied in four different doses (0, 100, 300 and 500 mgL -1 AVG) 4 weeks before the estimated harvest date. While the lowest values of total soluble solids content and pH were obtained from 500 mgL -1 AVG treatment, the highest values were obtained from control. The titratable acidity was higher in 500 mgL -1 AVG treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…In this study, the fruit removal force values for Santa Rosa plum measured was similar to that reported by Ozturk et al. (2012 a,b); Ozturk et al (2013). Skin and flesh firmness gradually increased by increasing AVG doses reported by Ozturk et al (2012a).…”
Section: Mechanical Propertiessupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, the fruit removal force values for Santa Rosa plum measured was similar to that reported by Ozturk et al. (2012 a,b); Ozturk et al (2013). Skin and flesh firmness gradually increased by increasing AVG doses reported by Ozturk et al (2012a).…”
Section: Mechanical Propertiessupporting
confidence: 90%
“…Hue angle values for both skin and flesh apple fruits increased as AVG application doses increased from 0 to 500 mg L -1 , respectively. In this study, the fruit color characteristics values for Santa Rosa plum measured were similar to reported literature (Ozturk et al 2012b;Ozturk et al 2013). …”
Section: Color Characteristicssupporting
confidence: 90%
See 2 more Smart Citations
“…pH, TA, and TSSC for Fuji apple were 3.1, 0.4 %, 14.0% respectively by reported by Ozturk et al (2013a). Ozturk et al (2013b) reported that TA, pH, and TSSC for Braeburn apple were 0.86 %, 2.87, and 15.44%, respectively. In this study, for Japanese crabapple fruits, pH is similar to the results reported by Ozturk et al (2012b); Ozturk et al (2013b).…”
Section: Chemical Propertiesmentioning
confidence: 99%